2021
DOI: 10.3390/ijms22147400
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Connexin43 Stimulates Endothelial Angiogenesis Independently of Gap Junctional Communication In Vitro

Abstract: Connexins (Cx) form gap junctions (GJ) and allow for intercellular communication. However, these proteins also modulate gene expression, growth, and cell migration. The downregulation of Cx43 impairs endothelial cell migration and angiogenetic potential. Conversely, endothelial Cx43 expression is upregulated in an in vivo angiogenesis model relying on hemodynamic forces. We studied the effects of Cx43 expression on tube formation and proliferation in HUVECs and examined its dependency on GJ communication. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 48 publications
1
19
1
Order By: Relevance
“…Moreover, we observed that the knock-down of Cx43 in the endothelium in mouse aortas impaired the aortic vessel sprouting ex vivo. This is in line with the recently published study by Koepple et al, where Cx43 siRNA treatment impaired the ability of endothelial cells to form capillary like structures in vitro [ 5 ]. Of note, Koepple et al found the endothelial cell proliferation to be unaffected by Cx43, and therefore hypothesized that the angiogenesis promoting effect of Cx43 is derived from an influence on migration.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, we observed that the knock-down of Cx43 in the endothelium in mouse aortas impaired the aortic vessel sprouting ex vivo. This is in line with the recently published study by Koepple et al, where Cx43 siRNA treatment impaired the ability of endothelial cells to form capillary like structures in vitro [ 5 ]. Of note, Koepple et al found the endothelial cell proliferation to be unaffected by Cx43, and therefore hypothesized that the angiogenesis promoting effect of Cx43 is derived from an influence on migration.…”
Section: Discussionsupporting
confidence: 92%
“…Cx43 has been shown to influence cellular responses, independently of its gap junctional channel function [ 5 , 11 , 12 , 13 , 14 , 39 ]. We previously showed that the Cx43 channel independent function is important for cellular migration [ 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations